SKRINING TUBERKULOSIS (TB) PARU - Siti Rahmah; Citra Indriani; Agus Prihatmo Wisnuwijoyo (Politeknik Kesehatan Kemenkes Mamuju, 2017)
AFB positive detection cases increase in 2011 until 2013 at Sukoharjo District, but TB CDR is still below national and local targets. Nguter PHC has highest CDR among other subdistrict, that is 84.6% in 2012 and 68.9% in 2013. The objective of this study is screening pulmonary TB patients in Nguter PHC region. Target population screening was ≥ 15 years who often contact with AFB positive patients who in of September 2013 to 2014 period. We did screening by interview about clinical symptom and sputum examination. Diagnostic test are distribution and combination of clinical symptoms, microscopic examination of sputum in Nguter PHC, and cross check sputum to BBKPM Surakarta. The analysis are find the value of p, sensitivity, specificity, PPV, NPV, and Kappa value. We get 160 respondents. Results of microscopic examination of sputum find 15 people (9,38%) were AFB positive and prevalence is 9.38%. Clinical symptoms that have highest sensitivity is cough for 2-3 weeks or more (100%). Kappa value for the cross check is 80% (good deal) with an error rate of 6.67 rate . The screening helps capture suspected pulmonary TB much more (national target 5-15%). It is recommended that training on the management of TB laboratory analyst officers in all PHC so the value of the agreement (kappa) with BBKPM can be increased and the error rate can be decreased.